Airfoil With Membrane At Low Reynolds Number - Roslan, Abdul Qayyum (Universiti Sains Malaysia, 2019)
In this project, an experiment was carried out to study the aerodynamic performance on NACA 2412. The airfoil is divided into two parts which are airfoil with flexible membrane and rigid airfoil. The airfoils were fabricated using aluminium. A medical rubber sheet was used as the flexible membrane. By using flexible membrane, the airfoils have the ability to adapt to the incoming flows by changing their camber automatically, thus balancing the pressure differences on the upper and lower part of the airfoils to reduce the flow separation. The airfoils were tested in a wind tunnel. The velocities of the air flow are 6m/s, 9m/s, 12m/s and 15m/s. The test was carried out with angles of attack ranging from -5 degree to 25 degree. The airfoil section has a chord of 10cm and length of 30cm. The surface area is 0.03 square metre. Detailed descriptions of the experimental design, fabrication, setup and testing are included in the thesis. The data was analysed using PCD30A software. The results show that airfoil with flexible membrane has the better aerodynamic performance compared to the rigid airfoil. Airfoil with flexible membrane produces the highest aerodynamic efficiency which is 17.27. Flexible membrane airfoil also produces higher maximum lift coefficient and higher stall angle compared to rigid airfoil